Comparative Analysis Of Chlorine Levels (Cl2) In Rice Before And After Cooking With The Iodometry Method - Lidiawati, Dewi; Mubarak, Syarul; Padilla, Nur; Pare Rombe, Yunita (Hayyan Journal, 2024)
This study aims to determine the ratio of chlorine levels in rice before and after it is cooked using the iodometric method. This research was conducted on June 12 - July 7 2023 at the ITKeSMU Sidrap Chemistry Laboratory. The type of research conducted is laboratory experimental research to investigate certain symptoms or substances through tests and tests with quantitative examination using the iodometric method. Sampling in this study was carried out randomly by taking rice that has a intact shape, is not easily broken, rice has just been milled. The method test and the calculation of the average chlorine content in rice samples before and after cooking. The results showed that there was a large difference between the chlorine content in rice before cooking, which was an average of 127,16% and after cooking, which was an average pf 48,323%